Comparison of complications and long-term survival after minimally invasive esophagectomy versus open esophagectomy in patients with esophageal cancer and chronic obstructive pulmonary disease - Rong, Yu; Hao, Yanbing; Xue, Jun; Li, Xiaoyuan; Li, Qian; Wang, Li; Li, Tian (Frontiers in Oncology, 2022)
Objective To compare the complications and long-term survival of esophageal cancer patients with chronic obstructive pulmonary disease (COPD) after minimally invasive esophagectomy (MIE) versus open esophagectomy (OE) using propensity score matching (PSM). Methods Esophageal cancer patients who underwent esophagectomy at the Thoracic Surgery Department of the First Affiliated Hospital of Hebei North University from January 2010 to December 2018 were retrospectively enrolled. The incidence of postoperative complications and prognosis of the MIE (n = 132) and OE (n = 138) groups were compared. To reduce bias, 1:1 PSM was adopted for the analysis. Results The median disease-free survival (DFS) of the MIE and OE groups were 24 months and 26 months, respectively, and neither group reached median survival. There was no significant difference between the two groups in terms of 3-year DFS and overall survival (OS). The stratification of the patients on the basis of the percentage of estimated forced expiratory volume in the first second (%FEV1) did not result in significant differences in the survival rates. A total of 42 patients (50%) in the MIE group and 55 patients (65.48%) in the OE group experienced complications, and the difference was statistically significant (OR=0.527, 95% CI: 0.283–0.981, P=0.042). The incidence of acute COPD exacerbation (OR=0.213, 95% OR, CI: 0.068–0.666, P=0.004) and pulmonary atelectasis requiring bronchoscopic aspiration (OR=0.232, 95% OR, CI: 0.082–0.659, P=0.004) were significantly higher in the OE versus the MIE group. In addition, the distribution of the various grades of complications also differed significantly between the two groups (P=0.016). While the incidence of minor complications (≤Grade II) was similar in both groups (P=0.503), that of severe complications (≥Grade III) was markedly higher in the OE group (P=0.002) and the Grade-IIIa complications were predominant (P=0.001). The severity of complications was correlated with the postoperative duration of hospital stay in both groups (r=0.187, P=0.015). No significant difference was observed in the incidence of minor complications (≤Grade II) between the two groups following stratification on the basis of %FEV1, whereas severe complications were more frequent in the OE group among patients with %FEV1 between 60% and 70% (P=0.001<0.05). Conclusion There was no significant difference in the postoperative DFS and OS of esophageal cancer patients with COPD after undergoing MIE or OE. However, MIE significantly reduced the incidence of severe postoperative complications among patients with %FEV1 between 60% and 70%.